The Degree of Pracicing Leadership Skills among Kindergarten Teachers in Dawadmi Goverment from Their Point of View and Its Relationship to Some Variables - Al-Mutairi, AlJawhara Mardas; Al-Shammari, Nuha Mishaan; Al-Manjoumi, Atheer Saad (Journal of Educational and Psychological Sciences, 2025)
The study aimed to identify the level of leadership skills among kindergarten teachers. The descriptive approach was used, and the study population consisted of all kindergarten teachers in the Dawadmi Goverment in the Kingdom of Saudi Arabia, who numbered (390) teachers, and the study was applied to a sample of (218) kindergarten teachers. The leadership skills level scale prepared by the researchers was used. The results showed that there was a high level of leadership skills among kindergarten teachers in Dawadmi Goverment, as well as the level of leadership skills dimensions among kindergarten teachers in Dawadmi Goverment ranged between high and very high, where time management skills came in first place at a very high level, followed by communication, social interaction and negotiation skills in second place at a very high level, then in third place after problem-solving skills at a high level, while emotional control and self-control skills came in fourth and last place at a high level. The results also showed statistically significant differences in the level of leadership skills assessment among kindergarten teachers in Dawadmi Goverment attributed to the educational qualification variable in favor of those who obtained a bachelor’s degree, as well as for the variable of the number of training courses in favor of teachers participating in five courses or more. The results also showed no statistically significant differences in the level of skills assessment Leadership among kindergarten teachers in Dawadmi Goverment is attributed to the variable of years of experience.